Diseño, captura y mapeo geo informático de la parroquia Buenavista utilizando tecnología assisted global possitioning system en la plataforma libre openstreetmap para dar a conocer su división política a nivel mundial.” - Bersoza Valarezo, Jimmy Bladimir (2015)
The Buenavista parish has several problems to publicize their tourist, sports venues, streets and important sites (churches, educational units, vestry, upc, fire, etc.), but the main problem was that these places were not known tourists and stakeholders in the sector. This problem has been the need to "design, capture and map geoinformáticamente the Buenavista parish using Global assisted technology possitioning system in the free platform openstreetmap and thus to publicize their political division worldwide through the Internet," he said Geoinformático mapping helped to show and locate the tourist sites, sports sites, sites of importance and streets, allowing optimize the times of people arriving or want to get somewhere, to have a global view of the whole parish on a map Geoinformático. For the development of this project the global assisted technology possitioning system was used to establish communication with satellites satellite positioning and thus allow capture, convert to GPX format and upload to servers OSM (Openstreetmap), traces the Osmtracker software tool, also free Openstreetmap web platform was used for mapping traces through its map editing tool which allows you to edit and create new maps through traces increases. Tests correctness check and correct mapping performed them with the application Offline maps, which allows download maps and facts of OSM and store on a mobile device for a tour with GPS without having internet connection, all the tools set forth above are licensed Open Source. Therefore the implementation of this Geoinformático map Buenavista parish and can be viewed from anywhere in the world via internet, for anyone using maps Geoinformation for their trips, viewing the sights, important sites, streets and sports venues of the same